The Association between Teeth Loss and Oral Health Problems (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The teeth play various functional roles, from the most basic functions to more subtle functions.One of the most tragic events that can happen to the teeth are loss it, as a result trauma or dental diseases.Tooth loss has esthetic, functional, positional and psychological impacts on the life of individuals.Objectives: To investigate the association between tooth loss and oral health problems among partiallyand completely edentulous patients. Method: (Questionnaire and Clinical Examination). Self-administeredquestionnaire was distributed to the patients to collect information relating to demography and cause oftooth loss, in addition to mastication and speech state after tooth loss. Four clinical conditions includingsupra-eruption, drifting teeth, temporomandibular disorders and bone resorption were used to recognize theeffects of missing teeth. Patients seeking dental treatment at General Hospital, Morzuk, Libya were recruitedfor the study. Criteria included age of 16 years and above with one or more missing teeth except for thirdmolars. Results: altogether 58 participants, 31 (53.4 %) were males while 27 (46.6%) were females. Theparticipants were aged 16–>45 years, among them, 44 patients (75.9%) are partially edentulous, and 14patients (24.1%) were completely edentulous. The patients with complete teeth loss and the patients withmissing both the anterior and posterior teeth are most groups suffer problems among patients who involvedin the study. patients who loss posterior teeth are the lowest group had, suffer of health problems due to lossof teeth among all of them.The general relationship between tooth loss and the oral health problems was positive and strong. Conclusions:there are statistically significant relationship between tooth loss and oral health problems, where the strongvalue of this relationship (0.614) and significance within less than (0.05).
Keywords: Tooth loss, consequences of tooth loss, causes of tooth loss.